2014
DOI: 10.1007/s12010-013-0705-1
|View full text |Cite
|
Sign up to set email alerts
|

Medium Initial pH and Carbon Source Stimulate Differential Alkaline Cellulase Time Course Production in Stachybotrys microspora

Abstract: The production profile of cellulases of the mutant strain A19 from the filamentous fungus Stachybotrys microspora was studied in the presence of various carbon sources (glucose, lactose, cellulose, carboxymethylcellulose (CMC), and wheat bran) and a range of medium initial pH (5, 7, and 8). Two extracellular cellulases from the Stachybotrys strain (endoglucanases and β-glucosidases) were monitored by enzymatic assay, sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and zymogram analysis. Glucose and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The critical values that represented the maximum b-glucosidase activity as high as 1483.27 U/mL were observed when the amount of carbon source and pH were increased up to a certain extent, at approximately 10% (w/v) and pH 7.3, respectively ( Figure 5). The outcome seen here is reflected in its positive value (+142.75BD) ( Table 2) and corroborated an earlier study by Al-Jazairi et al [52], in which the activity of b-glucosidase produced by Brettanomyces lambics was the highest when the fungus was cultured at both high pH and high content of carbon source.…”
Section: Effect Of Carbon Sources and Phsupporting
confidence: 91%
“…The critical values that represented the maximum b-glucosidase activity as high as 1483.27 U/mL were observed when the amount of carbon source and pH were increased up to a certain extent, at approximately 10% (w/v) and pH 7.3, respectively ( Figure 5). The outcome seen here is reflected in its positive value (+142.75BD) ( Table 2) and corroborated an earlier study by Al-Jazairi et al [52], in which the activity of b-glucosidase produced by Brettanomyces lambics was the highest when the fungus was cultured at both high pH and high content of carbon source.…”
Section: Effect Of Carbon Sources and Phsupporting
confidence: 91%
“…It revealed that expression of some cellulase genes may need some special induced conditions and there may be expression of some cellulase genes under presence of other carbon source, like glucose. For Stachybotrys microspore A19, carbon sources and the pH of the culture medium can direct a differential induction of various cellulases (such as endoglucanases and beta-glucosidases; Ben Hmad et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Biochemical results showed that higher rates of enzyme activities were obtained for a basic pH of about 8 [15]. However, for the first condition (W1), we kept the pH neutral.…”
Section: Study Of the Production Of The Enzymatic Activities In Liquimentioning
confidence: 99%